The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1271/bbb.60674
|View full text |Cite
|
Sign up to set email alerts
|

The Last Twenty Residues in the Head Domain of Mouse Lamin A Contain Important Structural Elements for Formation of Head-to-Tail Polymersin Vitro

Abstract: Nuclear lamins are a type of intermediate filament (IF) proteins. They have a characteristic tripartite domain structure with a alpha-helical rod domain flanked by non-alpha-helical N-terminal head and C-terminal tail domains. While the head domain has been shown to be important for the formation of head-to-tail polymers that are critical assembly intermediates for lamin IFs, essential structural elements in this domain have remained obscure. As a first step to remedy this, a series of mouse lamin A mutants in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…Unlike cytoplasmic IFs, lamin dimers tend to form paracrystals in vitro rather than 10-nm filaments Herrmann and Foisner 2003;Melcer et al 2007). In addition to the central rod domain (Schirmer et al 2001;Strelkov et al 2004), it has been shown that the head and tail domains are also involved in lamin assembly (Sasse et al 1998;Stuurman et al 1998;Herrmann and Foisner 2003;Shumaker et al 2005;Isobe et al 2007). Although A-and B-type lamins appear to interact with each other in vitro (Georgatos et al 1988;Ye and Worman 1995;Schirmer and Gerace 2004), little is known about the composition and structure of lamin polymers within the lamina, and even less is known about their nucleoplasmic structures.…”
Section: Lamins As Structural Components Of the Nucleusmentioning
confidence: 99%
“…Unlike cytoplasmic IFs, lamin dimers tend to form paracrystals in vitro rather than 10-nm filaments Herrmann and Foisner 2003;Melcer et al 2007). In addition to the central rod domain (Schirmer et al 2001;Strelkov et al 2004), it has been shown that the head and tail domains are also involved in lamin assembly (Sasse et al 1998;Stuurman et al 1998;Herrmann and Foisner 2003;Shumaker et al 2005;Isobe et al 2007). Although A-and B-type lamins appear to interact with each other in vitro (Georgatos et al 1988;Ye and Worman 1995;Schirmer and Gerace 2004), little is known about the composition and structure of lamin polymers within the lamina, and even less is known about their nucleoplasmic structures.…”
Section: Lamins As Structural Components Of the Nucleusmentioning
confidence: 99%
“…This initial process is dependent on the head domain of lamin A (Isobe et al, 2007;Spann et al, 1997), thus proteins that bind with high affinity to the N-terminus of lamin A/C are expected to inhibit their assembly. Here, we have identified DARPins that specifically bind to the head domain and coil 1A (amino acids 1-62) of human lamin A, with Lys32 as an amino acid that is crucial for their binding ( Fig.…”
Section: Binding Of Darpins To the Head Domain Of Lamin A Inhibits Asmentioning
confidence: 99%
“…8, step 3) (14). Notably, Ser 22 is also a phosphorylation site of CDK1 (45). The CDK1 phosphorylation sites of the lamin types are part of conserved sequence stretches.…”
Section: Nec-associated Protein Kinases Pul97 and Pkc Trigger Regulatmentioning
confidence: 99%
“…The CDK1 phosphorylation sites of the lamin types are part of conserved sequence stretches. For lamin B, the respective phosphorylated residues are Ser 23 (lamin B1) and Ser 17 (lamin B2) (45). Lamins A and C are subject to alternative splicing of the LMNA gene and share the same N-terminal sequence, including the CDK1/pUL97 phosphorylation site.…”
Section: Nec-associated Protein Kinases Pul97 and Pkc Trigger Regulatmentioning
confidence: 99%